New records and an updated list of snakes (Squamata: Serpentes) from Xuan Lien nature reserve, Thanh Hoa province, Vietnam - Tan, Nguyen Van; Cuong, Pham The; Truong, Nguyen Quang (Academia Journal of Biology, 2016)
we report six new records of snakes from thanh hoa province based on newly collected specimens from xuan lien nature reserve, comprising three species of colubridae (lycodon futsingensis, l. meridionalis and oreocryptophis porphyraceus), two species of natricidae (hebius boulengeri and parahelicops annamensis), and one species of elapidae (bungarus slowinskii). in addition, an updated list of 38 snake species from xuan lien nature reserve is also provided. the snake fauna of xuan lien nature reserve contains a number of species of conservation concern including six species listed in the governmental decree no. 32/2006/nd-cp (2006), eight species listed in the vietnam red data book (2007), and four species listed in the iucn red list (2016).